The Influence of Job Satisfaction and Leadership Style on Employee Performance Mediated by Organizational Citizenship Behavior: Penelitian - Yusrin; Buyung Sarita; La Ode Asfahyadin Aliddin (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to analyze the influence of job satisfaction and leadership style on employee performance, both directly and indirectly through organizational citizenship behavior (OCB) as a mediating variable. This study uses a quantitative approach with the type of explanatory research. Data collection was carried out through a questionnaire of 34 employees of the South Konawe Regency Health Office who were selected by census. The data analysis method used is Partial Least Square Structural Equation Modeling (PLS-SEM). The results of the study show that job satisfaction and leadership style have a positive and significant effect on employee performance. In addition, job satisfaction and leadership style also have a significant effect on OCB. Meanwhile, OCB itself has proven to have a positive influence on performance. Other findings show that OCB mediates the influence of job satisfaction and leadership style on employee performance. The implications of this study emphasize the importance of human resource management in paying attention to the psychological aspects of employees and the effectiveness of leadership styles to encourage extra work behaviors that support the improvement of organizational performance, especially in public services in the health sector.